THE INFLUENCE OF FAMILY ENVIRONMENT, PEER ENVIRONMENT, AND LEARNING INTEREST ON STUDENTS' LEARNING OUTCOMES IN CLASS X OF BASIC ACCOUNTING AT SMK NEGERI JAKARTA TIMUR - Anis Alfi; Unggul Purwohedi; Dwi Kismayanti Respati (Yayasan Education and Social Center, 2023)
Research was conducted with the aim to find out the influence of the family environment on student learning outcomes, the influence of the peer environment on student learning outcomes, and the effect of interest in learning on student learning outcomes. Research is intended for class X students of basic accounting subjects in the accounting and financial skills program at East Jakarta State Vocational School. The reachable the affordable population for this research is 178 students consisting of class X students at 46 State Vocational Schools Jakarta, 40 State Vocational Schools Jakarta, 50 State Vocational Schools Jakarta. The sample of this research is 122 students. total over sample was chosen according to the Isaac and Michael formula, with an error rate of 5%. This study uses a sampling technique a proportional random sampling technique. The data obtained via method uses the questionnaire method for the independent variable, while the dependent variable uses secondary data in the form of an Odd Semester End Assessment. Data processing is done by performing data analysis techniques including multiple regression equation, analysis data requirements test, classical assumption test, model feasibility test, and hypothesis test. The decision on the results of processing the research data is there is a positive and significant influence between the family environment on learning outcomes, there is a positive and significant influence between the peer environment on learning outcomes, and there is a positive and significant influence between learning interest on learning outcomes. The coefficient of determination in this study is 23.8%.